(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to explore the current landscape of research on Environmental, Social, and Governance (ESG) Performance through a Systematic Literature Review (SLR) and bibliometric analysis using data retrieved from the Scopus database as of October 11, 2025. A total of 1,186 articles were identified after applying screening criteria, including publication type, language, and accessibility. The findings reveal a significant rise in ESG-related publications since 2020, with a sharp increase between 2023 and 2025, reflecting the growing global relevance of sustainability research. China emerged as the dominant contributor to ESG literature, followed by the United Kingdom, Italy, Malaysia, South Korea, and Indonesia. The bibliometric visualization using VOSviewer identified strong international collaborations and recurring key themes such as sustainability, corporate governance, innovation, and corporate social responsibility. The results confirm that ESG Performance remains a highly dynamic and influential research domain, essential for advancing both academic theory and corporate practice. This study provides an integrated overview of how ESG Performance contributes to sustainable business strategies, while also highlighting gaps related to measurement standardization and theoretical integration, offering valuable insights for future research development. Keywords: ESG performance;